2001
DOI: 10.5694/j.1326-5377.2001.tb143555.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of coeliac disease in a population‐based study from Western Australia: a case for screening?

Abstract: Objectives To determine the prevalence of coeliac disease in an Australian rural community. Design Retrospective analysis of stored serum samples from 3011 random subjects from the Busselton Health Study. IgA antiendomysial antibodies (AEA) were detected by indirect immunofluorescence, and subjects testing positive were contacted and offered small‐bowel biopsy. Main outcome measures Prevalence of AEA positivity and biopsy‐proven coeliac disease in the community with reference to the proportion of symptomatic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 2 publications
2
47
2
1
Order By: Relevance
“…Studies have suggested that the prevalence of CD in most countries studied is approximately 1%5 6 and about 30% of these communities carry susceptibility genes for CD HLA DQ2 (20% of Caucasians, North Africans, South and West Asians) or HLA DQ8 (10% of all Caucasians and Asians). These genes are found less commonly in some ethnic groups (pure Chinese, Japanese, Afro-Caribbean or Sub-Saharan African descent) where CD is less common 7.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have suggested that the prevalence of CD in most countries studied is approximately 1%5 6 and about 30% of these communities carry susceptibility genes for CD HLA DQ2 (20% of Caucasians, North Africans, South and West Asians) or HLA DQ8 (10% of all Caucasians and Asians). These genes are found less commonly in some ethnic groups (pure Chinese, Japanese, Afro-Caribbean or Sub-Saharan African descent) where CD is less common 7.…”
Section: Epidemiologymentioning
confidence: 99%
“…(6) However, real differences may also exist between regions(7) and races, as higher levels of CD have also been shown outside Europe and the US among populations of predominantly European extraction (e.g., New Zealand and Australia). (13, 14)…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the number of reported cases in the Netherlands increased from 0.18 per 1000 live births from 1975–1990, to 0.54 per 1000 live births 1993–1994 [1]. There is also increasing recognition that symptomatic coeliac disease may be the tip of the iceberg, with many more asymptomatic cases in the community [2-4]. …”
Section: Introductionmentioning
confidence: 99%
“…In a population based screening study from a rural community of Western Australia, 10/3001 were positive for anti-endomysial antibodies. This community was of predominantly Anglo-Celtic origin [4]. Australians come from diverse ethnic backgrounds, thus the prevalence reported in this community cannot be generalised to the Australian population.…”
Section: Introductionmentioning
confidence: 99%